Evidence for marine influence in the Lower Jurassic Precipice Sandstone, Surat Basin, eastern Australia. Issue 1 (2nd January 2018) - Martin, M.; Wakefield, M.; Bianchi, V.; Esterle, J.; Zhou, F.
ABSTRACT: The Lower Jurassic (Sinemurian to Pliensbachian) Precipice Sandstone is the oldest formation and a regional aquifer in the Surat Basin, straddling southeast Queensland and northern New South Wales. Time-equivalent units are recorded in the Eromanga (Poolowanna Formation) and Clarence-Moreton (Ripley Road /Helidon Formation) basins. The Precipice Sandstone is generally considered to consist of braided channel deposits, which upwards become increasingly sinuous or meandering and ultimately give way to a lacustrine succession—the Evergreen Formation. Marine influence has been proposed by some, for parts of the Evergreen Formation. The transition from the Precipice Sandstone to the conformably overlying Evergreen Formation is gradual and diachronous leading to stratigraphic nomenclature inconsistency around the boundary. During sedimentological description of the Precipice Sandstone core from one of QGC Pty's ground water wells (Woleebee Creek GW4) 'tidal' features (flaser and wavy bedding, synaeresis cracks, clay drapes and Lockeia traces) were recorded. Biostratigraphy samples contained 'brackish' or coastal margin flora supporting the tidal interpretation. Although not sampled for biostratigraphy, similar 'tidal' facies have been noted where the Precipice Sandstone crops out in the Carnarvon Gorge section of Carnarvon National Park (Queensland), ∼200 km from the Woleebee Creek GW4 well, suggesting widespread development of a tidal system or systems. The Precipice Sandstone can be divided into an upper and lower unit; each has a distinct sedimentological and electric or wireline-log character, which are described and have been mapped in over 750 wells across the Surat Basin.